(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
This paper is based on a presentation delivered during the First World Congress for Existential Psychotherapy held in London in May 2015. It explores the issue of thrownness and freedom in relationship to authenticity. Our ability to claim ownership of our givens, our thrownness, is an act of free will which allows us to ’be who we are’ and to ’love our destiny’. In order to understand our psychological givens different developmental theories are integrated in what is termed, the ’DNA of the Soul’. Finally, it is proposed that certain developmental milestones have similar counterparts in the psychotherapeutic process.